PERENCANAAN TAHUNAN LEMBAGA PENDIDIKAN DALAM KERANGKA PEMBANGUNAN PENDIDIKAN NASIONAL - Ramdhani, Iqbal; Ega Rismasita; Siska Septia Ulfa; Kasinyo Harto; Fitri Oviyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Annual planning in educational institutions is a key element in supporting national education development, particularly in aligning school operations with national visions such as the Merdeka Curriculum. This article aims to analyze how annual planning can be optimized to enhance access, quality, and relevance of education in Indonesia. Using a qualitative literature review approach, this study examines the concept of annual planning, implementation challenges, and its relationship with national education indicators based on academic and policy sources from 2015 to 2025. The findings indicate that effective annual planning facilitates programs such as teacher training and project-based learning, but is hindered by resource limitations, regional disparities, and a lack of managerial capacity. Technology, such as the Merdeka Mengajar platform, and participatory approaches can help overcome these barriers. This article recommends managerial training, cross-sector collaboration, and the use of technology to strengthen planning, supported by inclusive government policies. Further research is recommended to empirically evaluate the implementation of annual planning, especially in remote areas. This study offers theoretical insights and practical guidance for education administrators in realizing high-quality national education.